Undernutrition induces major alterations in the lipid droplets of white and brown adipose tissues in wistar rats. (August 2021) - Rodríguez-Rivera, Carmen; Santín Moreda, Laura; Alguacil, Luis F.; Escrivá, Fernando; Álvarez, Carmen; González-Martín, Carmen
Highlights: Several studies have shown a relationship between the distribution of fat mass around the organism, metabolic disorders, and an increased risk of morbidity and mortality. Studies related to weight and health have been more popular regarding obesity rather than extreme caquexia or calorico-proteic deficiencies, but these states are interesting from the point of view of the preferential atrophy of certain organs that may help us in the understanding of undernourishment. The discovery of beige adipose tissue has instigated thoughts around the roles played by the different cells in the adipose tissue as well as its adaptability in pathological states. A morphometric, morphologic, and quantitative study of the adipose tissue in an animal model based on a 40−50% diet restriction in comparison to control animals has been carried out. Differences in the studied parameters have been found, leading to the possibility of a transformation in between the types of adipose tissues, and that could be caused by an adaptive phenomenon to the undernourished state. Abstract: Several studies have shown a relationship between the distribution of fat mass around the organism, metabolic disorders, and an increased risk of morbidity and mortality. It has been demonstrated that in obese animals there is a big rise in the white fat deposits due to hyperplasia and hypertrophy of the adipocytes. Studies related to weight and health have been more popular regarding obesity rather than extreme caquexia or calorico-proteic deficiencies, but these states are interesting from the point of view of the preferential atrophy of certain organs that may help us in the understanding of undernourishment. Moreover, the discovery of beige adipose tissue has instigated thoughts around the roles played by the different cells in the adipose tissue as well as its adaptability in pathological states. In our study we carried out morphometric, morphological, and quantitative measurements of the adipose tissue in an animal model based on a 40−50% diet restriction in comparison to control animals. We have found a decrease in the size of white adipocytes together with a variation in the lipid droplet size of brown adipocytes in undernourished animals, what may be considered as possible transformations between the types of adipose tissues, and that could be caused by an adaptive phenomenon to the undernourished state.